Professores de Química no processo ensino-aprendizagem de estudantes com deficiência visual: Formação e prática - Gomes, Alceni de Brito (2019)
Special education from an inclusive perspective presents a challenge to teachers who teach students with disabilities. Teacher education should address situations in which knowledge of specific methodologies and curriculum adaptations are required. In this sense, the discussion about the particularities that permeate the relations between teacher education, chemistry teaching and visually impaired people is fundamental. The present study has as main objective to investigate the conception that the teachers of Chemistry of the Federal Institute of Paraíba - IFPB (Campina Grande Campus - PB) have about the process of inclusion of students with visual impairment in Chemistry classes. This is a qualitative study, since this type of methodology provides broader results when considering the context of the object analyzed. The analyzed data were obtained with a semi-structured interview. This study took place in 2018 and seven teachers of chemistry at the IFPB Campina Grande-PB participated in this study. The analysis methodology employed was based on the Content Analysis proposed by Laurence Bardin (2006). Regarding chemistry teachers, the results point to the importance of initial and continuous training in the field of special education, especially in the inclusive perspective. From this point of view, it is also essential to perform curricular adaptations and pedagogical materials in order to favor the teaching-learning process of chemistry content for students with visual impairment. The lack of comprehensive teacher education, especially as regards Special and Inclusive Education, creates obstacles to the inclusion proposal. Therefore, it is necessary to redefine the models of teacher education, in order to collaborate with a teaching practice that addresses the educational needs of students with visual impairment.